Moltitudini e solitudini. Eremiti e folle tra i secoli XII e XIII - Roberto Gamberini (Artes)
The mysticism of Francis of Assisi is closely linked to the hermitic experience that he and some of his companions underwent in the early years of their religious vocation and that they had continued to practice, alternating periods of public apostolate with periods of withdrawal from secular society. This inclination to hermitism is in line with the widespread tendency of the time towards individual religiosity, although in reality such religious attitude did not necessarily entail total isolation. Although many of the hermits living between the 12th and 13th centuries wanted to fill a need for escape and protest and navigated in a controversial space, fluctuating between recognition and marginalization, some of them attracted crowds and also carried out apostolic activity through preaching. However, the relationship between public life and hermitic isolation is delicate and involves its share of problems: the Church displays a cautious stance towards it and the Franciscan Order tries in various ways to maintain the balance embodied by its founding father.